Post-operative stereotactic radiosurgery versus observation for completely resected brain metastases: a single-centre, randomised, controlled, phase 3 trial. Issue 8 (August 2017) - Mahajan, Anita; Ahmed, Salmaan; McAleer, Mary Frances; Weinberg, Jeffrey S; Li, Jing; Brown, Paul; Settle, Stephen; Prabhu, Sujit S; Lang, Frederick F; Levine, Nicholas; McGovern, Susan; Sulman, Erik; et al.
Summary: Background: After brain metastasis resection, whole brain radiotherapy decreases local recurrence, but might cause cognitive decline. We did this study to determine if stereotactic radiosurgery (SRS) to the surgical cavity improved time to local recurrence compared with that for surgical resection alone. Methods: In this randomised, controlled, phase 3 trial, we recruited patients at a single tertiary cancer centre in the USA. Eligible patients were older than 3 years, had a Karnofsky Performance Score of 70 or higher, were able to have an MRI scan, and had a complete resection of one to three brain metastases (with a maximum diameter of the resection cavity ≤4 cm). Patients were randomly assigned (1:1) with a block size of four to either SRS of the resection cavity (within 30 days of surgery) or observation. Patients were stratified by histology of the primary tumour, metastatic tumour size, and number of metastases. The primary endpoint was time to local recurrence in the resection cavity, assessed by blinded central review of brain MRI scans by the study neuroradiologist in the modified intention-to-treat population that analysed patients by randomised allocation but excluded patients found ineligible after randomisation. Participants and other members of the treatment team (excluding the neuroradiologist) were not masked to treatment allocation. The trial is registered with ClinicalTrials.gov, number NCT00950001, and is closed to new participants. Findings: Between Aug 13, 2009, and Feb 16, 2016, 132 patients were randomly assigned to the observation group (n=68) or SRS group (n=64), with 128 patients available for analysis; four patients were ineligible (three from the SRS group and one from the observation group). Median follow-up was 11·1 months (IQR 4·8–20·4). 12-month freedom from local recurrence was 43% (95% CI 31–59) in the observation group and 72% (60–87) in the SRS group (hazard ratio 0·46 [95% CI 0·24–0·88]; p=0·015). There were no adverse events or treatment-related deaths in either group. Interpretation: SRS of the surgical cavity in patients who have had complete resection of one, two, or three brain metastases significantly lowers local recurrence compared with that noted for observation alone. Thus, the use of SRS after brain metastasis resection could be an alternative to whole-brain radiotherapy. Funding: National Institutes of Health.